A STUDY ON MIGRATORY PATTERN AND SOCIO-ECONOMIC STATUS OF TIRUCHY BLACK SHEEP IN TAMIL NADU - P. Gopu; N. Murali; R. Saravanan; R. Annalvilli (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Tiruchy Black is one of the coarse wool breeds of sheep reared in Tamil Nadu. An investigation was undertaken to ascertain the migratory pattern and socio-economic status of Tiruchy Black sheep at 71 flocks in 53 villages of Dharmapuri and Krishnagiri Districts of Tamil Nadu. The migratory tracts were almost regular over the year in the breeding tract. A total of eight migratory tracts comprising of three major and five minor tracts were identified. The overall distance covered was 98.64 ± 1.13 km with a range of 15 to 128 km. The mean radial migratory distance was 184.12 ± 1.42 with range from 65 to 234 in major tracts and 34.12 ± 1.62 with a range of 15 to 64 Km in minor tracts. The Tiruchy Black sheep farmers family size was comprised of 2-5 numbers and both the genders were involved in sheep rearing. In the present study, it was observed that vast majority of sheep farmers belonged to the most backward (72.16 %), followed by backward (22.37 %) and others (5.47 %). Majority of sheep farmers belonged to the ‘Kurumba Gounders’ (96.00%). A small proportion of them in small farms belonged to the Vanniyars (4.00%). Statistical analysis revealed no significant relation between caste, community and farm size. Depending upon the condition of the animal, prices of adult rams and ewes varied from Rs. 7,000 to 8,000 and from Rs.5000 to 6,000 respectively. Surplus ram lambs were sold at the age of 3 to 5 months for Rs.1,750 to 2,500. It is concluded that the Tiruchy Black sheep farmers were following traditionally migratory pattern over the generations and which helps improves their socioeconomic status in the breeding tract of Tamil Nadu.